2015
DOI: 10.1192/bjp.bp.113.140046
|View full text |Cite
|
Sign up to set email alerts
|

Word use in first-person accounts of schizophrenia

Abstract: Differences in pronouns suggest decreased self-focus or perhaps even an understanding of self as other in schizophrenia. Differences in how perceptual and causal words are correlated suggest that long-held delusions represent a decreased coupling of explanations with sensory experience over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
3
27
1
4
Order By: Relevance
“…However, Reddit posts that do not have these restrictions may reflect more natural language of users and allow for additional observations such as differences in punctuation usage. In line with the hypothesis put forth by Fineberg et al (2015) our finding that users with SZ use punctuation significantly less than CTL users may reflect more disorganized use of language, a prominent symptom of schizophrenia (Covington et al, 2005;APA, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…However, Reddit posts that do not have these restrictions may reflect more natural language of users and allow for additional observations such as differences in punctuation usage. In line with the hypothesis put forth by Fineberg et al (2015) our finding that users with SZ use punctuation significantly less than CTL users may reflect more disorganized use of language, a prominent symptom of schizophrenia (Covington et al, 2005;APA, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Though none of the subjects demonstrated overt distress during or after the task, we expected that they may have experienced implicit distress due the periods of volatile and untrustworthy advice in the task, or after hearing at the end that the confederate was not in fact another player, and that we had intentionally misled them. As a measure of implicit distress, we measured self-referential language (words like I, me, and mine), which has been demonstrated to increase with depression, suicidality, and other mental and physical illnesses (15, 18) (19). Control subjects did not change their use of self-referential language rom before to after the post-task disclosure, but BPD subjects used significantly fewer self-referential words after the disclosure (Figure 2C, time × group interaction F = 6.16, p = 0.02), suggesting that their distress actually decreased after it was revealed that they were interacting with a computer, rather than a human confederate.…”
Section: Resultsmentioning
confidence: 99%
“…We expected that people (and BPD > control) would experience implicit distress due the periods of volatile and untrustworthy advice in the task, or after hearing at the end that the confederate was not in fact another player, and that we had intentionally misled them. We measured implicit distress by counting self-referential language (words like I, me, and mine), as they are known to increase with distress in mental and physical illnesses (13, 14) (15).…”
Section: Introductionmentioning
confidence: 99%
“…There is a fairly robust literature showing that increased use of first-person singular pronouns (I, me, my) is associated with increased depression or suicidality (Fineberg et al, 2015;Stirman and Pennebaker, 2001;Zimmermann et al, 2016), indicating we may expect to see a negative association between hope and this type of pronoun. Conversely, there is some literature to show use of first-person plural pronouns, such as "we," could indicate a sense of social connectedness (Tausczik and Pennebaker, 2010), giving reason to expect a positive association with this type of pronoun.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there is some literature to show use of first-person plural pronouns, such as "we," could indicate a sense of social connectedness (Tausczik and Pennebaker, 2010), giving reason to expect a positive association with this type of pronoun. Research is less clear in guiding our expectations of associations with hope for second person (you, your) and third-person singular (she, he) and plural (they) pronouns, but studies have shown differences in the use of pronouns across categories in people with schizophrenia as compared to healthy controls and people with depression (Fineberg et al, 2015;Hong et al, 2015;Lee et al, 2007). Thus, while we had hypotheses for first-person singular and plural pronouns, analyses examining other types of pronouns were considered exploratory.…”
Section: Introductionmentioning
confidence: 99%